Exploring English Teaching Strategies: A Case Study at SMPN 2 Mori Atas - Tosinde, Nining Pratiwi; Modjanggo, Vivin Krismawanti (Sintuwu Maroso Journal of English Teaching, 2025)
Abstract: This research aims to investigate the teaching strategies employed by English teachers at SMPN 2 Mori Atas. Using a descriptive qualitative design, data were collected through observations, interviews, and documentation. The findings reveal that the teacher used three primary teaching strategies: direct instruction, small group work, and role play. Among these, direct instruction was the most frequently implemented. The study highlights the importance of selecting strategies that are both engaging and suited to students’ needs to enhance learning outcomes. These results contribute to a better understanding of how strategic teaching practices influence English language instruction at the junior high school level.